Analisis SWOT Pada Pengembangan Perbankan Syariah di Indonesia - Muslim Marpaung; Isnaini Harahap; Usnandar Afriansyah (Jurnal Ilmiah Ekonomi Islam, 2022)
This study will try to answer how the process of developing Islamic banking in Indonesia is currently. This research is a descriptive qualitative research. Data analysis technique using matrix and SWOT analysis. The results of the study indicate that an alternative strategy for developing Islamic banking in Indonesia is a strategy to maintain and defend. The current strenght is that Islamic financial institutions are more crisis resistant. The current weakness is the relatively small and limited fund capital and the lack of a workforce who understands the concept of Islamic baniking. The current opportunity is the merger of 3 national banks ( BNI Syariah, BRI Syariah, BSM) to become BSI. The current threat is decline in people's income due to the COVID-19. The urgency of handling power in the future is to prioritize the support of muslims. The urgency of handling weaknesses in the future is the relatively smaller and limited capital of funds. The urgency of handling future opportunities is the merger of three national banks ( BRI Syariah, BNI Syariah and BSM). The urgency of handling threats in the future is the reduction in people's income due ti due COVID-19 pandemic. Keywords : Islamic Banking, Analysis SWOT, and Islamic Economic